2022
DOI: 10.18632/aging.203895
|View full text |Cite
|
Sign up to set email alerts
|

Construction and validation of a prognostic risk model of angiogenesis factors in skin cutaneous melanoma

Abstract: Melanoma can secrete tumor angiogenesis factors, which is the essential factor for tumor growth and metastasis. However, there are few reports on the relationship between angiogenesis factors and prognosis risk in melanoma. This study aimed to develop a prognostic risk model of angiogenesis for melanoma. Forty-nine differentially expressed angiogenesis were identified from the TCGA database, which were mainly involved in PI3K/Akt pathway, focal adhesion, and MAPK signaling pathway. We then establish an eleven-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…More recently, it has become a prevalent problem in cancer research to establish prognostic pro les based on gene sets associated with speci c biological characteristics (Tang et al, 2022;Wen et al, 2023;Zou et al, 2022).It is commonly known that the ability of doctors to make decisions and carry out individualized treatment plans can be enhanced by precisely predicting prognosis by grouping patients into high-risk or low-risk groups based on dependable predictive criteria. Therefore, in this study, we comprehensively and systematically constructed NRGs-based signatures and further anatomized their practical clinical value to support the essential preclinical signi cance of the neurotransmitter eld in cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has become a prevalent problem in cancer research to establish prognostic pro les based on gene sets associated with speci c biological characteristics (Tang et al, 2022;Wen et al, 2023;Zou et al, 2022).It is commonly known that the ability of doctors to make decisions and carry out individualized treatment plans can be enhanced by precisely predicting prognosis by grouping patients into high-risk or low-risk groups based on dependable predictive criteria. Therefore, in this study, we comprehensively and systematically constructed NRGs-based signatures and further anatomized their practical clinical value to support the essential preclinical signi cance of the neurotransmitter eld in cancer research.…”
Section: Discussionmentioning
confidence: 99%
“…The angiogenesis translation studies in CRC reveal that several angiogenesisrelated variables may be linked to prognosis [35]. Previous studies con rm that tumor angiogenesis is regulated by numerous genes with extremely complex interactions between these geness [15,36,37]. In the era of cancer precision medicine, multi-gene approaches can better describe tumor biology characteristics and guide clinical decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating of studies have strongly con rmed that the role of angiogenesis-related genes (ARGs) in the development of solid tumor, including CRCr [12][13][14]. Zou et al constructed a model based on ARGs classi cation in skin cutaneous melanoma (SKCM) to help stratify patients and predict prognosis and immunotherapy response [15]. To our knowledge, no studies have been reported on the prognostic features of CRC from the perspective of ARGs.…”
Section: Introductionmentioning
confidence: 99%